A Comparison Between Two Methods for Teaching Forearm Defense in Volleyball and Determining the Transfer of Learning from an Instructional Setting to a Game-Like Setting - Khitam Mousa Ay (European Scientific Journal, ESJ, 2016)
This study aims to make a comparison between two different methods (the Bottom-up method and the Top-down method) for teaching forearm defense in volleyball and determining the transfer of learning from an instructional setting to a game-like setting. The subjects of the study were (36) students at physical education faculty in the university of Jordan, with mean age of (20 ± 0.5) years, who were assigned in volleyball course (2) in the second semester 2015/2016. They were divided randomly into two groups: The Bottom-up method group (18) students, and the Top-down method group (18) students. Two different (4-weeks) programs were applied, three times per week for (50 minutes) by the same physical education teacher; the author of this study who is specialized in teaching volleyball, (12) lessons plans were prepared for each group in which the subjects learned the forearm defense skill and how to use this skill under game conditions. Two measurements were taken; both groups were measured at the beginning (pre-test) in order to establish that all students started at the same level of skill performance and under game-like conditions performance. After the completion of the teaching program, the final measurements were taken (post-test) to note the different impact between the two methods of teaching on the subject`s performance in forearm defense skill performance and game-like conditions. Statistical analysis by using the (SPSS) program was done, included T-test for mean at pre and post test for the two groups and T-test for mean at post test between the two groups. The results showed significant differences (p < 0.05) in post test between the two groups in favor of the Bottom-up method group in forearm defense skill performance in volleyball. Whereas, the results showed significant differences (p < 0.05) in post test between the two groups in favor of the Top-down method group in transfer performance to a game-like setting. The study concluded that it is important to use the combination of both methods; both methods have merit according to the stage of motor learning.